2000
DOI: 10.1074/jbc.275.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent Gene Expression Mediated by MEF2 Transcription Factors

Abstract: Ca2؉ induction of a subset of cellular and viral immediate-early activation genes in lymphocytes has been previously mapped to response elements recognized by the MEF2 family of transcription factors. Here, we demonstrate that Ca 2؉ activation of MEF2 response elements in T lymphocytes is mediated in synergy by two Ca 2؉ /calmodulin-dependent enzymes, the phosphatase calcineurin, and the kinase type IV/Gr (CaMKIV/Gr), which promote transcription by the MEF2 family members MEF2A and MEF2D. Calcineurin up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
161
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 56 publications
9
161
0
1
Order By: Relevance
“…3) [72]. As in other systems, MEF2-dependent transcription in T cells is activated by Ca 2þ signals and by ectopic expression of activated CaMK IV, calcineurin, or ERK5/BMK1 [73][74][75].…”
Section: Biological Roles Of Class Iia Hdacsmentioning
confidence: 92%
“…3) [72]. As in other systems, MEF2-dependent transcription in T cells is activated by Ca 2þ signals and by ectopic expression of activated CaMK IV, calcineurin, or ERK5/BMK1 [73][74][75].…”
Section: Biological Roles Of Class Iia Hdacsmentioning
confidence: 92%
“…(ii) Binding of calcineurin-activated NF-AT to MEF2D. NF-AT, a well-known calcineurin substrate in non-activated T cells, translocates from the cytosol into the nucleus where it forms a ternary complex with MEF2 and p300, leading to full activation of Nur77 expression (Blaeser et al, 2000;Youn et al, 2000a).…”
Section: Menin Represses Jund Transcriptional Activity In Protein Kinmentioning
confidence: 99%
“…Mitogen-activated protein kinases stimulate MEF2 transcriptional activity through phosphorylation of the MEF2 transactivation domain (11,12). The calcium͞calmodu-lin-dependent phosphatase calcineurin activates MEF2 by a posttranslational mechanism that may require association of MEF2 with the nuclear factor of activated T cells transcription factor (13)(14)(15)(16). Recently, we reported that calcium͞calmodulin-dependent protein kinase (CaMK) signaling stimulates MEF2 activity by disrupting MEF2-HDAC complexes, with resulting export of HDAC5 from the nucleus to the cytoplasm (10,17).…”
mentioning
confidence: 99%